Place, Power and Sexual/Gender Irony: Indonesian Archipelagic and Islandic Selves - Hamzić, Vanja (2012)
This paper interrogates the resilient ironies of gender/sexual pluralism in Indonesia, which challenge and resist both heteronormative and homonormative identitary scripts. It presents an anthropological account of subjectivity formation and negotiation wherein specific sexual/gendered ethnoscapes result in complex and dis-universal archipelagic and islandic selves.